Layered Plaque in Organic Lesions in Patients With Coronary Artery Spasm - Takeshi Nishi; Teruyoshi Kume; Ryotaro Yamada; Hiroshi Okamoto; Satsohi Koto; Masahiro Yamashita; Masahiko Ueno; Kyo Kamisaka; Yoshitaka Sasahira; Ayano Enzan; Yasuyuki Sudo; Tomoko Tamada; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Coronary artery spasm plays a vital role in the pathogenesis of coronary plaques. We sought to investigate the plaque characteristics of co‐existing organic lesions in patients with coronary artery spasm in comparison to those without coronary artery spasm by intracoronary optical coherence tomography (OCT). Methods and Results We included 39 patients who presented with a symptom suspected of coronary spastic angina and had an organic lesion, defined as ≥plaque burden of 50% assessed by OCT. Coronary artery spasm was diagnosed by positive acetylcholine provocation test, or by spontaneous spasm detected during coronary angiography. A total of 51 vessels with an organic lesion were identified. Of these, coronary artery spasm was observed in 30 vessels (spasm), while not in 21 vessels (non‐spasm). Organic lesions in the spasm vessels, compared with those in the non‐spasm vessels, had a higher prevalence of layered plaque (93% versus 38%, P<0.001), macrophages (80% versus 43%, P=0.016), and intraplaque microchannels (73% versus 24%, P<0.001), and lower prevalence of macrocalcification (23% versus 62%, P=0.009) as assessed by OCT. Conclusions Layered plaque, macrophages, and intraplaque microchannels, were frequently observed in organic lesions in patients with coronary artery spasm. These findings suggest that coronary artery spasm induces local thrombus formation as well as active inflammatory response, therefore increasing the risk of rapid plaque progression and ischemic events in patients with coronary artery spasm.